2017
DOI: 10.1177/0956797616686855
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Attention Between Visual Dimensions as a Source of Switch Costs

Abstract: Task-switching experiments have documented a puzzling phenomenon: Advance warning of the switch reduces but does not eliminate the switch cost. Theoretical accounts have posited that the residual switch cost arises when one selects the relevant stimulus-response mapping, leaving earlier perceptual processes unaffected. We put this assumption to the test by seeking electrophysiological markers of encoding a perceptual dimension. Participants categorized a colored letter as a vowel or consonant or its color as "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 29 publications
1
22
2
Order By: Relevance
“…One caveat to note is that in our face perception task expression was relevant with respect to the response categories -emotional and neutral expressions were mapped onto the two responses in the face task. In the study by Elchlepp et al (2017), which showed that switching from the letter task prolonged colour processing, the ERP contrast based on the frequency (probability) of colour presentation was orthogonal (incidental) to the required 'warm/cold' colour classification (the manipulation of colour probability was also not mentioned to participants before or during the experiment). Similarly, in Elchlepp et al's (2015) Experiment 1, which showed that the ERP effect of word frequency was delayed by a switch from the perceptual (colour symmetry) task to the lexical task and strongly attenuated in the perceptual task, the lexical frequency contrast was orthogonal to the semantic categorisation task (and it was not mentioned to participants until the post-experiment debriefing).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One caveat to note is that in our face perception task expression was relevant with respect to the response categories -emotional and neutral expressions were mapped onto the two responses in the face task. In the study by Elchlepp et al (2017), which showed that switching from the letter task prolonged colour processing, the ERP contrast based on the frequency (probability) of colour presentation was orthogonal (incidental) to the required 'warm/cold' colour classification (the manipulation of colour probability was also not mentioned to participants before or during the experiment). Similarly, in Elchlepp et al's (2015) Experiment 1, which showed that the ERP effect of word frequency was delayed by a switch from the perceptual (colour symmetry) task to the lexical task and strongly attenuated in the perceptual task, the lexical frequency contrast was orthogonal to the semantic categorisation task (and it was not mentioned to participants until the post-experiment debriefing).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we sought to minimise the face-letter spatial separability by: (1) superimposing relatively large transparent letter outlines on faces (see Figure 1), and (2) varying the exact size of the letter and its location on the face, whilst ensuring that the letter was always superimposed on a substantial portion of the eyes-nosemouth region of the face. Our reasoning (analogous to that of Elchlepp et al, 2015 andElchlepp et al, 2017) is that if perceptual encoding of emotional expression is independent of task-set we should find its electrophysiological 'signature' (the EEE) uninfluenced by switching from the letter task. Our analyses will also further interrogate the "automaticity" of recognition of emotional expression.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…We estimated the s-LRP latency difference between fast and slow change RT waveforms using a cross-correlation method (Elchlepp, Best, Lavric & Monsell, 2016). This method does not return an onset latency for each waveform but a value representing how much in time one waveform has to be shifted to achieve a maximal correlation with the other waveform.…”
Section: Methodsmentioning
confidence: 99%
“…500 ms in Experiment 1) to ensure that there was ample time for participants to reorient their attention (see e.g. Elchlepp, Best, Lavric, & Monsell, 2017).…”
Section: Methodsmentioning
confidence: 99%